Development and Encapsulation of Affibody-Apoferritin Biologics for the Targeted Treatment of Breast Cancer - Holden, Isobel R (2025)
Targeted cancer therapies produce more favourable clinical outcomes for cancer patients compared to unselective small-molecule cytotoxic chemotherapeutics. Currently, the most widely available targeted anti-cancer therapies are antibody-drug conjugates (ADC) with an example being tratuzumab-DM1 (Kadcyla®) which is a first line treatment for human epidermal growth factor 2 (HER2, ErbB-2) positive breast cancer. To develop a new improved biological anti-cancer therapy and drug delivery system, a fusion protein has been constructed, composed of a small 5 kDa affibody targeted towards an ErbB receptor: EGFR (ErbB-1), HER2 (ErbB-2) or HER3 (ErbB-3) and attached via a flexible glycine-serine linker at the N-terminus of a subunit of human heavy chain apoferritin. This creates a hollow spherical affibody-apoferritin nanocage (8 nm internal diameter) with 24 targeting affibodies displayed in an ordered pattern on the cage surface (14 -15 nm external diameter).